2014
DOI: 10.1016/j.sbspro.2013.12.970
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Social Commerce Acceptance in Lithuania

Abstract: The growing use of online social networks becomes more attractive for many companies as it presents opportunity to reach consumers. The possibility to access users' data basing on their preferences and interest allow companies target their marketing actions to particular segments. Companies pay high attention to social commerce, which can be defines as "a subset of electronic commerce that involves using social media, online media that supports social interaction, and user contributions to assist in the online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 18 publications
3
31
0
6
Order By: Relevance
“…section 2), the factor usefulness is examined in 13 studies. 12 studies (e.g., Featherman and Hajli, 2015;Hajli, 2012;Kim, 2015;Noh et al, 2013;Shen, 2012a) define the variable as usefulness or perceived usefulness and 1 study (Gatautis and Medziausiene, 2014) uses the conceptually similar variable performance expectancy, which is part of the Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al, 2003). In these studies, usefulness has been confirmed to influence the use (7/8), purchase (3/3), and information disclosure (1/1) intention/behavior.…”
Section: Findings On the Factors And Their Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…section 2), the factor usefulness is examined in 13 studies. 12 studies (e.g., Featherman and Hajli, 2015;Hajli, 2012;Kim, 2015;Noh et al, 2013;Shen, 2012a) define the variable as usefulness or perceived usefulness and 1 study (Gatautis and Medziausiene, 2014) uses the conceptually similar variable performance expectancy, which is part of the Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh et al, 2003). In these studies, usefulness has been confirmed to influence the use (7/8), purchase (3/3), and information disclosure (1/1) intention/behavior.…”
Section: Findings On the Factors And Their Effectsmentioning
confidence: 99%
“…Both factors have been examined in 8 studies. Different forms of social influence have been investigated such as normative social influence (also conceptualized as subjective norm or normative belief) and informational social influence (e.g., Featherman and Hajli, 2015;Gatautis and Medziausiene, 2014;Kwahk and Ge, 2012;Shin, 2013;Xi et al, 2016). Derived from the TRA (cf.…”
Section: Findings On the Factors And Their Effectsmentioning
confidence: 99%
“…Afrasiabi Rad & Benyoucef (2011) proposed that social commerce is developed from "one-to-one interaction" e-commerce, with more social attributes and social interaction. Compared with traditional e-commerce, social commerce pays more attention to network, collaboration, information sharing and other elements, followed by sales (Gatautis & Medziausiene, 2014). made a comparative analysis of the development of social commerce from four dimensions of interpersonal relationship, management, technology and information.…”
Section: The Difference Between Social Commerce and Traditional E-commentioning
confidence: 99%
“…The usual practice is to refer to empirical formulas to calculate the estimated value of the hidden layer neurons. l n m a = + + (9) l represents the number of neurons in the hidden layer, m and n, respectively, stand for the number of neurons in the output layer and the input layer, and a is an arbitrary constant ranging from 0 to 10.…”
Section: Design Bp Neural Network Structurementioning
confidence: 99%